Women's Leadership and the Law of Choosing Women Leaders in the Perspective of Islamic Law and Positive Law - Gunawan Abdi (ISNU Sumatera Utara, 2024)
Women's leadership is an issue that continues to be debated in various societies, especially when associated with the perspective of Islamic law and positive law. In Islam, differences of opinion regarding women's leadership are often based on interpretations of verses of the Qur'an and hadith. One of the hadiths that is often used as a reference is